أحكام زواج القاصر في الفقة الإسلامي و القانون الوضعي - غزال, دعاء (University of Eloued جامعة الوادي, 2018)
"ملخص جاءت هذه الدراسة استقراء للأحكام الشرعية لزواج القاصر، ومقارنتها بأحكام القوانين الوضعية لبعض الدول العربية، مع تحليل بعض هذه النصوص القانونية، حيث قمت ببيان المقصود بهذا النوع من الزواج، ثم ركزت على أهم المسائل الخلافية الفقهية في الفقه الإسلامي عند الفقهاء المتقدمين والمتأخرين، كما سلطت الضوء على نظرة المشرع الجزائري لزواج القاصر، ثم ما جاءت به بعض قوانين الدول العربية، كما بينت أهم الآثار التي تترتب على هذا الزواج. وخلصت في الأخير إلى أن زواج القاصر جائز و مشروع، وللولي حق تزويج القاصر، لكن ذلك منوط بتوفر المصلحة، وأن تقنين سنّ الزواج في القانون فيه حفاظ على مصلحة حفظ النسل والنسب لا يتعارض مع شرعية هذا الزواج " " This study is an extrapolation of the legal provisions of the marriage for a minor and compared to the provisions of the laws that some Arab countries with the analysis of some of these legal texts, where I made a statement of this type of marriage, and then focused on the most important issues of jurisprudence in Islamic world the scholars advanced and late. Highlighted the Algerian legislator's view of the marriage for the minor and what some laws of the Arab countries have brought, as well as the most important implications of this marriage. And concluded that the marriage of the minor is permissible and legitimate, and the guardian has the right to marry the minor, but this is subject to the availability of interest, and legalization of the age of marriage in the law in order to maintain the interest of conservation of birth and descent does not conflict with the legitimacy of this marriage. "
مذكرة ماستر تخصص شريعة وقانون
Keywords: الزواج- القاصرات - الفقه الاسلامي - القوانين العربية; Marriage - Minorities - Islamic Jurisprudence - Arab Laws